Improving the Popularity of Syekh Abdul Ghofur Tomb as Potential Religious Tourism Destination in Cugenang Cianjur - Noventya Widyanuri; Alvina Gracela Rama Djati; Devara Mirrah Dalila; Muhammad Setiawan Kusmulyono; Dini Anggraeni Sirad; Ni Luh Eva Ardonis (MITRA: Jurnal Pemberdayaan Masyarakat, 2020)
Tomb tourism objects are often regarded as segmented tourism objects for certain people looking for spirituality. This activity makes it difficult for tomb tourism objects to become popular tourist attractions. The tomb of Sheikh Abdul Ghofur is one of the religious tourism which so far can be enjoyed by only a handful of people who know of its existence. The long story of Sheikh Abdul Ghofur in spreading Islam in Cianjur Regency is a wealth of ancestral history that benefits all elements of society. Therefore, through the community service program of the School of Business and Economics (SBE), Prasetiya Mulya University, the tomb of Sheikh Abdul Ghofur was packaged to make it more popular and accessible to all groups. The main focus of increasing its popularity was to strengthen the story and to make it available on the internet such as providing an explanation of the location of the tomb through the Google Maps application and making tourist booklets to install signage. This effort was fully implemented so that the Tomb of Sheikh Abdul Ghofur could now be accessed by various groups to maintain history in the Cianjur Regency.